Advances in global sourcing. Models, governance, and relationships : 7th Global Sourcing Workshop 2013, Val d'Isère, France, March 11-14, 2013, Revised Selected Papers - Kotlarsky, Julia; Willcocks, Leslie P.; Oshri, Ilan (Lecture Notes in Business Information Processing, 2013)
This book contains 13 papers from the 7th Workshop on Global Sourcing, held in Val d'Isère, France, during March 11-14, 2013, which were carefully reviewed and selected from 40 submissions. They are based on a vast empirical base brought together by leading researchers in information systems, strategic management, and operations. This volume is intended for students, academics, and practitioners interested in research results and experiences on outsourcing and offshoring of information technology and business processes. The topics discussed represent both client and supplier perspectives on sourcing of global services, combine theoretical and practical insights regarding challenges that both clients and vendors face, and include case studies from client and vendor organizations.